Effectiveness of indigenous Rhizobium sp. isolates from peatland soils on soybean (Glycine max L. Merril) growth and production - Gunawan Tabrani; Isna Rahma Dini; Handoko Suryo Purnomo (Universitas Lancang Kuning, 2023)
The low productivity of soybeans can be overcome by cultivating them on peatlands, accompanied by the provision of indigenous Rhizobium strains derived from peatlands. Isolating Rhizobium sp. from peatlands is believed to enhance soybean productivity on such land. This study aims to determine the effectiveness of local Riau Rhizobium sp. isolates for soybean cultivation in Riau peatlands. Six isolates of Rhizobium sp. were used in this study, obtained from plants growing on peatlands: IIMB4, IIRM1, IIRM2 from the rhizosphere of Mucuna bracteata, and IIRA4, IIRA2, IIRA6 from the rhizosphere of Acacia crassicarpa. The experiment followed a completely randomized design (CRD), with each treatment replicated four times. The treatments included control, commercial Rhizobium sp., isolates IIMB4, IIRA2, IIRA6, IIRM2, IIRA4, and IIRM1. The results demonstrated that all indigenous Rhizobium sp. isolates from peatlands, particularly IIMB4, effectively formed symbiotic associations with soybean plant roots, improving growth parameters and increasing soybean production. Nevertheless, it is also necessary to assess the effectiveness of these Rhizobium sp. isolates on various other leguminous plant species to identify the most efficient symbiotic isolates across different leguminous crops.